Studi Simulatif Pengaruh Sudut Kemiringan Sudu, Tip Speed Ratio dan Soliditas terhadap Faktor Daya Turbin Darrieus Dengan Profil Sudu NACA0021 - Abdulkadir Muhammad; Harianto; Dandung Rudy Hartana (Retii, 2019)
Performance of Darrieus turbines are influenced by many fators, among them are blade profile, blade angle of inclination (α), tip speed ratio (λ), and blade solidity (σ). The objective of the research is to investigate the influences of α, λ, and σ to the power factor (Cp) of a vertical Darrieus water turbine by mean of CFD FLUENT simulation. The simulation has been conducted in a 20 cm rotor diameter, 25 cm rotor length, 3 blades, NACA0021 blade profile vertical Darrieus water turbine. Blade lenght variations are 4 cm, 5 cm and 6 cm; blade angle of inclinatian variations are 00, 50 and 100; and rotor speed variations are 60 rpm, 80 rpm, 100 rpm, 120 rpm, 150 rpm, and 200 rpm. It is concluded from the research that maximum Cp is 3.2609 % achieved at σ = 0.9, λ = 1.0467 and α = 50.